Self-medication and its impacts on public health in Brazil (Research, Society and Development, 2025)
Self-medication is defined as the practice of taking medicinal substances without the advice and/or supervision of a qualified health professional with the intention of bringing benefits in the treatment of diseases or relief of symptoms. This study aims to analyze the prevalence of self-medication in Brazil and understand habits and patterns of consumption and context related to this practice. The methodology was based on a literature review with studies in several areas of health to identify determining factors and consequences of self-medication. Studies indicate that the prevalence of self-medication in Brazil is more frequent among women and the elderly. This inappropriate practice can generate undesirable effects and consequences, such as iatrogenic diseases, poisoning, drug interactions and also masking of progressive diseases, becoming a problem to be prevented and warned about. Some factors that facilitate self-medication in the country include easy access to over-the-counter medications, recommendations from family and friends, and a large number of pharmaceutical product advertisements that sell the idea of ​​"well-being" after using the product. Given the evidence gathered in the literature, self-medication in Brazil is a widespread practice that requires attention from authorities and health workers to promote the rational use of medications and raise awareness among the population about the seriousness of self-medication.